(untitled) (Journal of Asian Development Studies, 2025)
Coalition politics is typical in many democratic countries where the multi-party system prevails. However, the case of coalition politics in Pakistan has always been perplexing. M.A. Jinnah envisioned Pakistan as a democratic state. At the same time, the intrusion of civil-military regimes has caused confusion and complexity in the norms of politics and democracy. As an alternative, the opposition embraced coalition politics to achieve collective political gains—the unpacking of the political landscape and democratic conundrums showcasing the significance of the study. Therefore, the thematic deductive approach is applied in evaluating and analyzing qualitative and quantitative metadata to investigate how coalition politics in Pakistan impacted the norms of democracy and the future of democracy. This study aims to provide extensive insight into the evolution of coalition politics in Pakistan and unpacking the conundrums of democracy, focusing on the key themes and avenues for reforms. In findings, the civil-military regimes tried to foster the seeds of democracy, though some yielded bitter realities while others portrayed promising results. Conundrums, e.g. judicialization and establishmentarian of politics, socioeconomic disparities, political dogmatism and nationalistic apartheid, potentially erode the fundamentals of democracy. Contemporary precedents of coalitions, i.e. governments’ inclusivity, political dialogues and parliamentary progressions, portray the strength of democracy. Thus, the country needed comprehensive reforms in the socio-political and socioeconomic landscape to strengthen democracy.